Effect of salinity on granulation, performance and lipid accumulation of algal-bacterial granular sludge. (September 2019) - Meng, Fansheng; Liu, Dongfang; Huang, Wenli; Lei, Zhongfang; Zhang, Zhenya
Abstract: The effects of salinity (0–3%) on algal-bacterial granulation, nutrients removal and lipid production were studied in four identical sequencing batch reactors. Results demonstrated that high salinity (1–3%) enhanced biomass growth and granular settleability with little impact on organics removal and a slightly lower total P removal (57%) obtained. On the other hand, the activity of nitrifying bacteria was found to decrease with the increase of salinity, which was completely inhibited at the salinity of 3%, resulting in nitrite accumulation. No obvious change in lipid content was detected under the tested salinity levels, while its productivity was significantly increased under higher salinity conditions. The dominant lipid component, hexadecenoic acid at the salinity of 0%, shifted to oleic acid when the salinity was increased from 0% to 3%. In addition, high salinity favored the enrichment of Nitzschia rather than Stigeoclonium . Highlights: Algal-bacterial granular sludge was successfully cultivated at salinity of 0–3%. Nitrification capability decreased with the increase of salinity. High salinity enhanced lipid productivity while affected its composition. Nitzschia rather than Stigeoclonium dominated the reactors at salinity of 1–3%.